Organization of mental healthcare in Bosnia and Herzegovina during coronavirus disease 2019 pandemic - Pajević, Izet (Indian J Psychiatry, 2020)
BACKGROUND: Coronavirus disease 2019 (COVID-19), like any other pandemic, has imposed an unprecedented threat to physical and mental health to all nations, worldwide. There is no enough evidence in the literature in this area. The present study has been done to explore the organization of psychiatric services in Bosnia and Herzegovina (BH) to meet mental health needs of BH citizens during the particular restrictive measures caused by COVID-19 pandemic. MATERIALS: This online survey has been done for BH psychiatric institutions. Data were collected from psychiatric institutions in the mental health network of BH. A total of 38 complete responses have been received. RESULTS: Of 38 study participants, three were the departments of psychiatry in university clinical centers, two were psychiatric hospitals, four were psychiatric wards in general hospitals, 27 were community mental health centers, and two were institutes for alcoholism and drug addiction. During the pandemic, all services functioned on a reduced scale, adhering to measures to protect and self-protect both staff and service users. Protective equipment was provided to staff in some institutions in a timely and complete manner and in some in an untimely and incomplete manner. Consultative psychiatric examinations were mainly performed through telephone and online, where it exists as a standard patient monitoring protocol. The application of long-acting antipsychotics was continuous with adherence to restricted and protective measures. In opiate addiction replacement therapy services, substitution therapy was provided for a longer period to reduce frequent contacts between staff and patients. Individual and group psychotherapy continued in reduced number using online technologies, although this type of service was not administratively regulated. An initiative has been given to regulate and administratively recognize telepsychiatry by health insurance funds in the country. A number of psychological problems associated with restrictive measures and fear of illness have been reported by patients as well as by the professionals in mental healthcare teams. There were no COVID-19-positive patients seeking help from institutions that responded to the questionnaire. In one center, infected people with COVID-19 from abroad sought help through the phone. Only one involuntary hospitalization was reported. The involvement of mental health professionals in the work of crisis headquarters during the design of the COVID-19 pandemic control measures varies from satisfactory to insufficient. Education of staff, patients, and citizens was regular with direct instructions through meetings, press, and electronic media. CONCLUSIONS: During the COVID-19 pandemic in BH, all psychiatric services functioned on a reduced scale, adhering to measures to protect and self-protect staff and service users. All patients who asked for help have been adequately treated in direct inpatient or outpatient mental healthcare or online, despite telepsychiatric services not being recognized in health system in BH. There were neither infected patients nor staff with COVID-19 in the psychiatric institutions who responded in this research. A large-scale, multicenter study needs to be performed to get a broader picture and to guide us for future better service planning and delivery.